Examining User Satisfaction and Continuous Usage Intention of Digital Financial Advisory Platforms - Athapol Ruangkanjanases; Taqwa Hariguna (HighTech and Innovation Journal)
This study investigates the factors influencing user satisfaction (US) and continuous intention (CI) to use digital financial advisory platforms in Indonesia, focusing on perceived ease of use (PEU), perceived enjoyment (PE), and service quality (SQ). Data from 413 respondents were collected through an online survey and analyzed using structural equation modeling (SEM) with SmartPLS. Results revealed that PEU significantly influences PE (β = 0.923, t-value = 88.677, p < 0.001) and CI (β = 0.471, t-value = 13.950, p < 0.001), demonstrating the critical role of usability in enhancing user engagement. PE positively affects US (β = 0.211, t-value = 7.248, p < 0.001), while SQ strongly predicts US (β = 0.773, t-value = 29.423, p < 0.001). The strong impact of the US on CI (β = 0.518, t-value = 15.117, p < 0.001) highlights satisfaction’s importance for user retention. R-squared values of 0.851 for PE, 0.876 for US, and 0.878 for CI indicate substantial explanatory power. This study extends the Technology Acceptance Model (TAM) by integrating enjoyment and SQ, offering a comprehensive framework for understanding user behavior in digital finance. Findings underscore the need for user-friendly design, engaging features, and high service standards to enhance satisfaction and retention.